2021
DOI: 10.3390/ijerph182312741
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Frailty and Sleep Quality among Saudi Older Adults: A Community-Based, Cross-Sectional Study

Abstract: (1) Background: Prevalence of poor sleep quality and its association with frailty status among the aging population of Saudi Arabia has not been studied. Therefore, the main objective of the current study was to estimate the prevalence of poor sleep quality and investigate the association between poor sleep quality and frailty in Saudi older adults; (2) Methods: A total of 270 (mean age 69.9 ± 6.2) older adults from the Riyadh region were involved in the study. To measure sleep quality, the Arabic version of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…Sleep disruption may initially alter adipokines, increasing the risk of physical frailty through a direct effect on adipokines. Or sleep disruption may affect in ammatory pathways, which in turn can lead to physical frailty [35]. It had also been shown that sleep The results of this study showed that malnutrition was an important risk factor for cognitive frailty, with the risk of malnutrition and malnutrition being 1.08 and 2.68 times higher than the occurrence of cognitive frailty with good nutrition, which was consistent with the results of previous studies [8].…”
Section: Discussionsupporting
confidence: 91%
“…Sleep disruption may initially alter adipokines, increasing the risk of physical frailty through a direct effect on adipokines. Or sleep disruption may affect in ammatory pathways, which in turn can lead to physical frailty [35]. It had also been shown that sleep The results of this study showed that malnutrition was an important risk factor for cognitive frailty, with the risk of malnutrition and malnutrition being 1.08 and 2.68 times higher than the occurrence of cognitive frailty with good nutrition, which was consistent with the results of previous studies [8].…”
Section: Discussionsupporting
confidence: 91%
“…From the 59 eligible studies, a total of 20 studies were excluded following full-text review. Reasons for exclusion included: the absence of reported prevalence (n = 2) [ 25 , 26 ]; data collected before 2011 (n = 2) [ 27 , 28 ]; the study’s participants being restricted to a specific age group and not being representative of a whole population (n = 1) [ 29 ]; the population were children (n = 3) [ 30 , 31 , 32 ]; population was mixed and data could not be separated for the included population i.e., including Saudis and non-Saudis (n = 3) [ 33 , 34 , 35 ] or adults and children (n = 1) [ 36 ]; and studies with a scope irrelevant to the objectives of this review (n = 4) [ 37 , 38 , 39 , 40 ] or presenting findings that have been reported more than once (n = 4) [ 34 , 38 , 41 , 42 ]. Finally, 39 studies were included in this review ( Figure 1 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it makes older people more vulnerable to poor health outcomes [ 2 ]. Increasing life expectancy brings opportunities for older adults, their families, and societies [ 6 ], but a greater emphasis should be placed on identifying risk factors to avoid or reduce frailty in older adults—especially those with one or more chronic diseases [ 7 ]. The prevalence of frailty is much higher among older adults living in nursing homes than in community settings, and it is a significant predictor of mortality among older adults in nursing homes.…”
Section: Introductionmentioning
confidence: 99%